2000
DOI: 10.3758/bf03212061
|View full text |Cite
|
Sign up to set email alerts
|

Perception of musical tension for nontonal orchestral timbres and its relation to psychoacoustic roughness

Abstract: Can tension in nontonal music be expressed without dynamic or rhythmic cues? Perceptual theories of tonal harmony predict that psychoacoustic roughness plays an important role in the perception of this tension. We chose a set of orchestrated chords from a nontonal piece and investigated listeners' judgments of musical tension and roughness. Paired comparisons yielded psychophysical scales oftension and roughness. Two experiments established distinct levels ofthese two attributes across chords. A model simulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 31 publications
(34 reference statements)
1
30
3
Order By: Relevance
“…Audible beating, or roughness, often evokes strong unpleasant reactions in listeners, and is routinely used to modulate tension in music [31][32][33]. However, its aesthetic association does not appear to be learned from music-related experience, and we find little evidence for a relation to consonance.…”
Section: Discussioncontrasting
confidence: 49%
“…Audible beating, or roughness, often evokes strong unpleasant reactions in listeners, and is routinely used to modulate tension in music [31][32][33]. However, its aesthetic association does not appear to be learned from music-related experience, and we find little evidence for a relation to consonance.…”
Section: Discussioncontrasting
confidence: 49%
“…This result is important because the interplay of musical tension and relaxation is a critical element of the structure of tonal music ͑Lerdahl and Jackendoff, 1983͒. Even in nontonal music, in which tension and relaxation are not conveyed by traditional relationships among chords, Pressnitzer et al ͑2000͒ found that judgments of the roughness of chords were strongly correlated with judgments of tension. Thus, in both tonal and nontonal music, roughness plays a role in creating the tension so important for musical expression.…”
Section: Introductionmentioning
confidence: 73%
“…However, other low-level psychoacoustical features may play a role in mediating tension. In particular, sensory dissonance is likely to have an effect on experienced tension, which is indicated by previous research showing that for single chords subjective roughness ratings correlate with tension ratings (Pressnitzer, McAdams, Winsberg, & Fineberg, 2000) and that predictions of a roughness model correlate with tension ratings of musicians (Bigand et al, 1996). To investigate whether these findings generalize to longer music pieces, future research on musical tension should therefore consider also including measures of sensory dissonance into the analysis.…”
mentioning
confidence: 98%